PERSOALAN NAFKAH SEBAGAI PENYEBAB TERJADINYA PERCERAIAN DALAM PERSPEKTIF HUKUM KELUARGA ISLAM - Sri Hariati (The Juris, 2021)
This study aims to analyze the livelihood issues that cause divorce from the perspective of Islamic Family Law, and to analyze the legal consequences of divorce due to subsistence factors with the study of Mataram Religious Court Decision No: 0492 / Pdt.G / 2016 / PA.Mtr. The research method used is empirical normative legal research, with a case approach method, a statutory approach, and a sociological approach. The results of the research and discussion conclude that the issue of livelihood can be one of the causes of divorce in terms of Islamic family law due to 3 things, namely, Nyusyus 'husband, Nyusyus' wife, and syiqaq. Based on the facts in decision No: 0429 / Pdt.G / 2016 / PA.Mtr due to the legal consequences of divorce due to financial factors and other reasons, the court obliges the ex-husband to provide living expenses and / or determine an obligation for the ex-wife. Before the marriage between a husband and a wife candidate should be more solidified in terms of physical and spiritual preparation and to officials at the Religious Courts, so that they can decide cases related to this factor of living more carefully and quickly so as not to cause harm to either party.